Transformations of the Art Market in the World - Quantitative Approach - Joanna Bialynicka-Birula (Institute of Economic Research (IER), 2017)
The dynamics of the art market is usually presented using price perspective, price indexes for the market and financial returns. In this paper the value and volume approach is proposed, that haven't been considered in aggregative way for a longer period of time in the literature. The presentation of changes taking place in the global art market in the period 2002-2015 is the aim of the paper. The results of dynamic analysis of the art market have been presented, including the two approaches: value and volume of transactions. The impact of the global crisis on the art market has been considered. In order to present the changes on the global art market statistical indexes of dynamics (single base and chain indexes) have been used. Moreover the trend analyses have also been conducted for the value and volume of transactions on the art market. The sources of data on the global art market have come from Artprice, ArtTactic, TEFAF (The European Fine Art Foundation). In the analyzed period 2002-2015 the changes of sales on the global art market had in general increasing tendency. The value and volume of sales have reached their tops in 2007 and 2014. The art market has been touched considerably by economic recession in 2009, but in the next year it has already staged a recovery. The trend analyses have allowed describing the changes on the market by means of mathematical functions. The analyses have allowed identifying the countries with the largest share in the global art market. A particular attention has been paid to the existence of triad on the art market, including the countries of Europe, USA and China. It is noteworthy that Europe and USA have dynamically lost their market share in favor of China.
Keywords: C; C1; D4; F6; Z11; 330; art market; art economics; art; market analysis; cultural economics